Intracellular Signaling by Bile Acids (Journal of Bio-Science, 2014)
Bile acids, synthesized from cholesterol, are known to produce beneficial as well as toxic effects in the liver. The beneficial effects include choleresis, immunomodulation, cell survival, while the toxic effects include cholestasis, apoptosis and cellular toxicity. It is believed that bile acids produce many of these effects by activating intracellular signaling pathways. However, it has been a challenge to relate intracellular signaling to specific and at times opposing effects of bile acids. It is becoming evident that bile acids produce different effects by activating different isoforms of phosphoinositide 3-kinase (PI3K), Protein kinase Cs (PKCs), and mitogen activated protein kinases (MAPK). Thus, the apoptotic effect of bile acids may be mediated via PI3K-110?, while cytoprotection induce by cAMP-GEF pathway involves activation of PI3K-p110?/? isoforms. Atypical PKC? may mediate beneficial effects and nPKC? may mediate toxic effects, while cPKC? and nPKC? may be involved in both beneficial and toxic effects of bile acids.The opposing effects of nPKC? activation may depend on nPKC? phosphorylation site(s). Activation of ERK1/2 and JNK1/2 pathway appears to mediate beneficial and toxic effects, respectively,of bile acids. Activation of p38? MAPK and p38? MAPK may mediate choleretic and cholestatic effects, respectively, of bile acids. Future studies clarifying the isoform specific effects on bile formation should allow us to define potential therapeutic targets in the treatment of cholestatic disorders. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17647J. bio-sci. 20: 1-23, 2012